Alcohol use disorders in patients with obsessive-compulsive disorder: The importance of appropriate dual-diagnosis - Gentil, Andre F.; de Mathis, Maria Alice; Torresan, Ricardo C. [UNESP]; Diniz, Juliana B.; Alvarengat, Pedro; do Rosario, Maria Conceicao; Cordioli, Aristides V.; Torres, Albina Rodrigues [UNESP]; Miguel, Euripedes C. (Elsevier B.V., 2009)
Objective: To evaluate the prevalence and clinical associated factors of alcohol use disorders (AUD) comorbidity in a large clinical sample of patients with obsessive-compulsive disorder (OCD).Methods: A cross-sectional study including 630 DSM-IV OCD patients from seven Brazilian university services, comparing patients with and without AUD comorbidity. The instruments of assessment used were a demographic and clinical questionnaire including evaluation of suicidal thoughts and acts and psychiatric treatment, the Structured Clinical Interview for DSM-IV Axis I disorders (SCID-I), the Yale-Brown Obsessive-Compulsive Scale, the Dimensional Yale-Brown Obsessive-Compulsive Scale, the Brown Assessment of Beliefs Scale, the Beck Depression and Anxiety Inventories and the Clinical Global Impression Scale. Current or past alcohol and other psychoactive substances use, abuse and dependence were assessed using the SCID-I (section E) and corroborated by medical and familial history questionnaires.Results: Forty-seven patients (7.5%) presented AUD comorbidity. Compared to OCD patients without this comorbidity they were more likely to be men, to have received previous psychiatric treatment, to present: lifetime suicidal thoughts and attempts and to have higher scores in the hoarding dimension. They also presented higher comorbidity with generalized anxiety and somatization disorders, and compulsive sexual behavior. Substance use was related to the appearance of the first O.C. symptoms and symptom amelioration.Conclusions: Although uncommon among OCD treatment seeking samples, AUD comorbidity has specific clinical features, such as increased risk for suicidality, which deserve special attention from mental health professionals. Future studies focused on the development of specific interventions for these patients are warranted. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Obsessive-compulsive disorder; Alcohol use disorders; Alcohol abuse; Alcohol dependence; Comorbidity; Clinical sample